Sulfuric acid production plant from pyrite a plant design - Chua, Charlene Lynette; Engcoy, Ganther Philip; Gautane, Gillette Grace
Sulfuric acid is a strong mineral acid with a wide range of application such as raw material in fertilizer production and as solvent in metal extraction processes. It is commonly produced from sulfur mineral burning. Using elemental sulfur as raw material implicates high capital cost. Due to this, a proposal for sulfuric acid using pyrite as raw material which is a cheaper alternative is presented. Manufacturing of sulfuric acid is commonly done by using sulfur mineral as a raw material. But because of the expensive price of sulfur, substitutes to sulfur for the sulfuric acid production are constantly being studied. One of the known substitute widely used is pyrite. This is because pyrite can be sourced at a cheap price in pyrite abundant countries. The mineral pyrite is chemically known as iron sulfide with the formula FeS2. The mineral is one of the most common sulfide minerals. In the Philippines, sulfuric acid is constantly being outsourced from the countries. There is an increase in the demand locally as seen from the increase in the number of importations of sulfuric acid the country has. It was also seen that pyrite, one of the raw materials of the sulfuric acid production process, is abundant in the country. This has led the proponents to formulate a sulfuric acid plant based in the Philippines to supply the constant local demand of sulfuric acid as raw materials can already be sourced at low cost. Market data for sulfuric acid shows an increasing demand for this product in the succeeding years. The available data are supported by the increase in the demand for products that uses sulfuric acid. One of which is the fertilizer industry which has also an outlook for an increasing demand in the succeeding years. The increase in the fertilizer demand in seen by both the increase in purchasing capacity of people as shown by the consistent GDP growth. The design of the reactor used for pyrite burning was formulated using the kinetic data from the study done by De Yuso et. al. Optimization was done to determine which operating condition would yield the highest conversion at the lowest cost. It was seen that for the study, the most optimal operating condition was at the conversion of 0.35 which yield as 423 cubic meter reactor. Further processing of the sulfur oxide that leaves the reactor will be done. However, this paper will focus on the design of the reactor section. The remaining section, the converter and absorption tower sections, will not be designed but rather, current conventional data from various references will be used. Detailed design of each equipment are also computed. Operating conditions and flow rates of each stream were determined in the mass and heat balance. Additional equipment needed to improve the process ware added. Separation equipment were employed to remove the pyrite particles from the feed air and recycle it back to the reactor. A recycle section was also introduced to save up on the cost of raw materials as a lot of pyrite remains unreacted after the first pass through the reactor. The final process flow diagram and calculation were presented in the paper. Analysis of the capital and working cost of the plant is done. These costs were estimated using the working capacity of the plants. The rate of return of the plant was calculated to determine whether it really was a profitable project. Since the net present value of the plant is Php 34,840,249.67, payback time of 3.83 years and internal rate of return is at 51 percent, it proves that the plant truly is profitable.